The neutral layer offset of medium and thick plate by sub domain boundary element method during plate flattening. (October 2022) - Xing, Tong; Huang, Qingxue; Xiang, Jianmin; Gui, Hailian
Highlights: The neutral layer offset was obtained by SD-BEM. Compared with FEM, experiment and elastoplastic mechanics, the error between SD-BEM and experiment was smallest. The flattening process model by SD-BEM was built and the accuracy was improved. Abstract: The medium and thick plate was developed in modern industrial production. In the production process, the shape defects occurred easily and it could be straightened generally by flattening machine. However, due to the offset relationship between the geometric center layer and the stress neutral layer in the flattening process, the straightening force was inaccurate and the flattening accuracy was reduced. Therefore, there was an error between the flattening model and the actual process. In this work, the geometric center layer of medium thick plate was treated as the boundary, at the same time, the bending deformation in the plate was transformed into the elastic-plastic deformation of two connected regions. Afterwards, combined with the advantages of sub domain boundary element method, the stress state of geometric center layer was calculated accurately. Besides, the geometric center layer of medium thick plate does not coincide with the stress neutral layer was proved, meanwhile, the calculation formula of neutral layer offset was given and its variation law was discussed. Subsequently, the influence of neutral layer offset derived by boundary element method on straightening accuracy was studied through Abaqus software and bending experiment. The results indicated that the flattening results were closer to the experimental results by considering the neutral layer offset calculated by the boundary element method. The flatness error was less than 5% and the residual stress error was 8%, which could improve the flattening accuracy and optimize the flattening model.